The sugarcane borer Diatraea saccharalis (Fabr.) (Lep., Crambidae) and its parasitoids: a synchrony approach to spatial and temporal dynamics - Rossi, M. N.; Fowler, H. G. (Blackwell Verlag Gmbh, 2003)
A data set on Diatraea saccharalis and its parasitoids, Cotesia flavipes and tachinid flies, was analysed at five spatial scales-sugarcane mill, region, intermediary, farm and zone-to determine the role of spatial scale in synchrony patterns, and on temporal population variability. To analyse synchrony patterns, only the three highest spatial scales were considered, but for temporal population variability, all spatial scales were adopted. The synchrony-distance relationship revealed complex spatial structures depending on both species and spatial scale. Temporal population variability [SD log(x+1)] levels were highest at the smallest spatial scales although, in the majority of the cases, temporal variability was inversely dependent on sample size. All the species studied, with a few exceptions, presented spatial synchrony independent of spatial scale. The tachinid flies exhibited stronger synchrony dynamics than D. saccharalis and C. flavipes in all spatial scales with the latter displaying the weakest synchrony levels, except when mill spatial scales were compared. In some cases spatial synchrony may at first decay and then increase with distance, but the presence of such patterns can change depending on the spatial scale adopted.
Keywords: Cotesia flavipes; Diatraea saccharalis; spatial synchrony; tachinid flies; temporal variability